Fishery characteristics, population dynamics and the impacts of the invasive red swamp crayﬁsh (Procambarus clarkii) in the Nile River, Egypt - Sahar Fahmy Mehanna (Journal of Fisheries)
Alien intrusive species are one of the extreme pressures on biodiversity for their rapid reproduction and adaptation to new environments. Crayfish Procambarus clarkii entered Egyptian freshwater ecosystems at the beginning of 1980's. After many years of negative effects of its introduction onto the Egyptian waters, it became one of the commercially important species. Population parameters of P. clarkii are estimated based on 1355 specimens collected from the Nile off El-Minya during 2019–2020. The isometric growth of the species under the study is confirmed according to the obtained b-value of length–weight relationship (LWR). Annual sex ratio (female : male) was in favour of females with an annual sex ratio 1.44 : 1. The values of growth coefficient (K) and the asymptotic total length (L∞) were assessed for males, females and combined sexes. Using mortality estimates, the exploitation ratio was 0.64 year–1. Investigation of relative yield per recruit (Y'/R) and analysis of relative biomass per recruit (B'/R) for P. clarkii in the Nile off El-Minya provides the highest (Y'/R) at Emax = 0.81 and the E0.5 (utilisation level that preserves the spawner stock biomass at 50% of the virgin spawning biomass) was 0.38. From fisheries management point of view, the current exploitation level should be decreased to that maintain the spawning stock biomass (from 0.64 to 0.38).